Comparison of Various Graft Materials in the Reconstruction of Ossicular Chain in Patients with Chronic Otitis Media: A Prospective Hospital Based Study - Niaz Fakhruddin; Chethan Kumar Gangaiah; Gopakumar KP; Geogin George Thottan; Mon Noufal (Bengal Journal of Otolaryngology and Head Neck Surgery, 2017)
Introduction